1999
DOI: 10.1002/(sici)1521-4095(199903)11:5<398::aid-adma398>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Property: Increase in the Magnetic Interactions of Cd1-yMnyS Nano-Sized Particles with Decreasing Particle Size

Abstract: The relationship between particle size and bandgap energyin magnesium‐containing quantum dots is reported here for the first time. A reverse micellar process was used in the synthesis of the Cd1–yMnyS quantum dots, a procedure whereby the size and composition of the quantum dots can be independently controlled. This allowed detailed investigation of the magnetic interactions between Mn2+ ions and the electron bands of CdS, and between Mn2+ ions themselves, and of how these interactions vary with the size and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…Effort to understand extended spin interactions in the quantum confined regime has led to the revelation of host of rich physical phenomena including giant Zeeman splitting, , magnetic polaron, and zero field magnetizations . Theory , and experiments on low dimensional DMS have shown very interesting size dependent properties, specifically in achieving control over long-range spin coherence and spin polarization under weak magnetic field. , In spite of this success, properties of DMS nanocrystals have been quite controversial, as they are often plagued with matters related to the uniformity of dopant incorporation and hence the origin of the ferromagnetism from the magnetic clusters. In fact, several studies in bulk, thin films, and nanowires have shown the importance of uniform magnetic ion distribution. Though similar studies in QDs are unavailable, statistical analysis of doping with nonuniform distribution of magnetic ions shows that the cluster formation of magnetic elements on the surface or inside the semiconductor nanocrystals results in poor magnetic response from these QDs.…”
mentioning
confidence: 99%
“…Effort to understand extended spin interactions in the quantum confined regime has led to the revelation of host of rich physical phenomena including giant Zeeman splitting, , magnetic polaron, and zero field magnetizations . Theory , and experiments on low dimensional DMS have shown very interesting size dependent properties, specifically in achieving control over long-range spin coherence and spin polarization under weak magnetic field. , In spite of this success, properties of DMS nanocrystals have been quite controversial, as they are often plagued with matters related to the uniformity of dopant incorporation and hence the origin of the ferromagnetism from the magnetic clusters. In fact, several studies in bulk, thin films, and nanowires have shown the importance of uniform magnetic ion distribution. Though similar studies in QDs are unavailable, statistical analysis of doping with nonuniform distribution of magnetic ions shows that the cluster formation of magnetic elements on the surface or inside the semiconductor nanocrystals results in poor magnetic response from these QDs.…”
mentioning
confidence: 99%
“…In spite of its promises, and reports of Mn‐doped ZnS as early as in the year of 1994, and subsequent reports of other Mn‐doped semiconductor nanocrystals, early magnetic studies suggested near absence of any interactions between magnetic dopants, such as Mn 2+ , in II–VI semiconductor nanocrystal hosts, most probably due to the absence of any free carriers in presence of such isovalent dopants and the large separation between magnetic ions in the dilute limit . Thus, the effect of enhanced sp–d exchange interaction in modulating magneto–optic and magneto–electronic properties of DMS nanocrystals were not very successful till last decade.…”
Section: Magnetic Impurity Dopingmentioning
confidence: 99%
“…Erste vielversprechende Berichte über Mn‐dotiertes ZnS erschienen bereits 1994, weitere Studien über andere Mn‐dotierte Halbleiter‐Nanokristalle folgten rasch . Frühe magnetische Studien hatten gezeigt, dass praktisch keine Wechselwirkungen zwischen magnetischen Dotanden wie Mn 2+ in II/VI‐Halbleiter‐Nanokristallen auftreten, und als höchstwahrscheinliche Ursache wurde die Abwesenheit von freien Ladungsträgern beim Vorliegen solcher isovalenter Dotanden sowie der große räumliche Abstand der magnetischen Ionen angegeben .…”
Section: Dotierung Mit Magnetischen Verunreinigungenunclassified